Beyond Compliance-Based Governance: The Role of Social Intermediaries in Mitigating Forced Labour in Global Supply Chains - Wilhelm, Miriam; Bhakoo, Vikram; Soundararajan, Vivek; Crane, Andrew; Kadfak, Alin (Production and Operations Management, 2025)
Forced labour poses a significant challenge within global supply chains, yet traditional compliance-based governance based on auditing has proven to be ineffective in addressing this issue. Non-government organizations and worker rights organizations can serve as crucial allies in supporting and safeguarding workers by assuming the role of a 'social intermediary' (SI) between supply chain firms and workers. However, these external organizations often hold limited power within these supply chains. In our paper, we examine the sources of power that SIs can cultivate and utilize to lead successful interventions against forced labour in supply chains. Through a comparative case study involving three SIs and their collaborative efforts with a global seafood brand, we explore various forms of non-mediated power and their underlying origins. By establishing these connections, we shed light on the effectiveness (or lack thereof) of interventions against forced labour. Our research makes three contributions. First, we contribute to ongoing research on forced labour in supply chains by emphasizing the constructive role that SIs can play to protect vulnerable workers. Second, we address a critical gap in the existing literature concerning power of SIs in supply chain relations. More specifically, we specify sources and types of non-mediated power that SI can leverage to design effective interventions against forced labour. Third, by comparing unique data on two worker groups vulnerable to forced labour – vessel workers and workers in seafood processing – we provide much-needed insights into how working conditions in non-factory settings can still be regulated.